EFEITO DA MODIFICAÇÃO ENZIMÁTICA NAS PROPRIEDADES TÉRMICAS,REOLÓGICAS E ESTRUTURAIS DO AMIDO DE PINHÃO (Araucaria angustifolia) - Cordoba, Layse do Prado (2015)
Starch is used as an important energy source in human diet and furthermore, has numerous industrial applications, such as thickening, colloidal stabilizer, gelling, bulking agent, water retaining and viscosity agent. The pinhão, seed of Araucaria angustifolia (Bertol.) Kuntze, has a high starch content (between 68-72 g 100 g-1 dry matter), and was the object of this study. This work aims to analyze the pinhão starch (Araucaria angustifolia) in its native and enzymatically modified form through chemical composition, thermoanalytical techniques (Thermogravimetry and Differential Thermal Analysis - TG / DTA; Differential Scanning Calorimetry - DSC), structural techniques (Scanning Electron Microscope - SEM and X-ray Diffraction - XRD) and rheological (Rapid Visco Analyzer - RVA). The pinhão starch samples were extracted in laboratory by aqueous method and modified with an enzyme complex composed of α-amylase (EC 3.2.1.1), amyloglucosidase (EC 3.2.1.3) and aspergillopepsin 1 (EC 3.4.23.18). The hydrolysis occurred in the period of 12h, 24h and 36h at the temperature of 31 °C and pH 5.0. Through chemical composition, it was possible to quantify each component of pinhão starch. Through TG analysis, it was observed that enzymatic hydrolysis increased the thermal stability of the samples. In the DSC analysis a decrease of ΔHgel after enzymatic modification was noted. A decrease in retrogradation in all treated samples was observed utilising RVA. XRD analysis allowed to characterise the pinhão diffraction pattern as C-type, and using the micro-images (SEM), it was possible to study the structure and surface of starch granules. Thus it, was determined the thermal, structural and rheological properties of native and hydrolyzed enzymatically pinhão starch, for a future application in the food, pharmaceutical or paper industry.